2019
DOI: 10.1136/emermed-2019-208629
|View full text |Cite
|
Sign up to set email alerts
|

Quality of reporting in abstracts of RCTs published in emergency medicine journals: a systematic survey of the literature suggests we can do better

Abstract: ObjectiveWe investigated the association between the publication of the Consolidated Standards of Reporting Trials extension for abstracts (CONSORT-EA) and other variables of interest on the quality of reporting of abstracts of randomised controlled trials (RCTs) published in emergency medicine (EM) journals.MethodsWe performed a survey of the literature, comparing the quality of reporting before (2005–2007) with after (2014–2015) the publication of the dedicated CONSORT-EA in 2008. The quality of reporting wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…However, revision of journal requirements and author guidelines are likely to have driven some changes, for example, the requirement for IRB/Ethics Committee approval. It is notable, however, that the quality of reporting in abstracts of EM trials is not improved by the use of the Consolidated Standards of Reporting Trials extension for abstracts 25…”
Section: Discussionmentioning
confidence: 99%
“…However, revision of journal requirements and author guidelines are likely to have driven some changes, for example, the requirement for IRB/Ethics Committee approval. It is notable, however, that the quality of reporting in abstracts of EM trials is not improved by the use of the Consolidated Standards of Reporting Trials extension for abstracts 25…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review [58] and three studies have also explored journal endorsement of CONSORT [41,55,57], which we did not do. As stated previously, the time frame covered by our study is quite long, meaning that many of the journals are not published anymore, or the RCTs are only found in hard copy.…”
Section: Comparison With Other Studiesmentioning
confidence: 97%
“…Abstract adherence to CONSORT extensions has also been assessed for cardiology [50], ophthalmology [51], anaesthesiology [52], periodontal disease [42], orthodontics [43], migraine and headache [53], gerontology and geriatrics [54], emergency medicine [55], surgery [56], and pain management [57]. Not one of these speciality studies has found completeness of reporting for abstracts and mostly agree that there is poor reporting, low compliance, room for improvement, and interventions are needed.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…With the publication of CONSORT extension for abstract reporting (CONSORT-A), it was endorsed by the World Association of Medical Editors, the International Committee of Medical Journal Editors, and the Council of Science Editors (Chhapola et al, 2018). Studies have been conducted based on CONSORT-A to evaluate the quality of abstract reporting in different areas and certain specialties (Germini et al, 2019;Faggion & Giannakopoulos, 2012;Chow et al, 2018;Fang et al, 2020;Gallo et al, 2020). However, these studies indicated that the reporting quality of RCT abstracts are consistently suboptimal.…”
Section: Introductionmentioning
confidence: 99%